INTEGRASI TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE DALAM PERANGKAT PEMBELAJARAN TEMATIK KELAS 3 - Fias Kurnia Ratri (Universitas Ngudi Waluyo, 2021)
This study aims is to describe the integration of TPACK (Technological Pedagogical and Content Knowledge) in class 3 thematic learning device, theme 7 sub-theme 4 SDIT Pelita Hati. The type of research used in this research is descriptive qualitative. This research design is classified as content analysis research because it involves connecting or comparing findings with several criteria or theories. The research subjects used quota sampling, namely learning devices for class 3, theme 7 (Technology Development), sub-theme 4 (Development of Transportation Technology), 1st learning and 2nd learning. The data collection in this study uses a documentation technique which is then analyzed using data analysis techniques Miles, M.B, Huberman, A.M, (2014) which consists of three flow of activities that occur simultaneously, namely: data reduction, data presentation, and conclusion drawing. Based on the available data, each TPACK component has been integrated in the learning tools for class 3, theme 7, sub-theme 4, 1st lesson and 2nd lesson, SDIT Pelita Hati Randublatung. However, there are still some indicators of TPACK components that have not been integrated into learning tools. This is because several CK and PK components have not been implemented, thus affecting the integration of other TPACK components.